Osteoporosis and sarcopenia-related traits: A bi-directional Mendelian randomization study - Liu, Chao; Liu, Ningyuan; Xia, Yu; Zhao, Ziyue; Xiao, Tao; Li, Hui (Frontiers in Endocrinology, 2022)
ABSTRACT Background: With the advancement of world population aging, age-related osteoporosis (OP) and sarcopenia (SP) impose enormous clinical and economic burden on society. Evidence from accumulating studies indicates that they mutually influence one another. However, observational study may be affected by potential confounders. Meanwhile, Mendelian randomization (MR) study can overcome these confounders to assess causality. Objectives: To evaluate the causality between OP and SP, informing new strategies for prevention, diagnosis and treatment of osteosarcopenia. Methods: Instrumental variables (IVs) at the genome‐wide significance level were obtained from published summary statistics, inverse variance weighted method and several other MR methods were conducted to evaluate the bi-directional causality between SP and OP. Myopia was analyzed as a negative control outcome to test the validity of IVs. Results: Femoral neck bone mineral density (FN BMD), lumbar spine BMD (LS BMD) and forearm BMD (FA BMD) had a direct causal effect on appendicular lean mass (ALM) [FA BMD related analysis: odds ratio (OR) = 1.028, 95% confidence interval (CI) = (1.008,1.049), p = 0.006; FA BMD related analysis: OR (95% CI) = 1.131(1.092,1.170), p = 3.18E-12; LS BMD related analysis: OR (95% CI) = 1.080(1.062,1.098), p = 2.86E-19]. ALM had a significant causal effect on LS BMD [OR (95% CI) = (1.033,1.147), p = 0.001]. There was no evidence for causal association between BMD and low‐grip strength. Conclusions: OP and SP might mutually have a significant causal effect on each other. Our results supported that the patient with severe OP was more susceptible to lose ALM and severe ALM loss might reduce LS BMD. Keywords: osteoporosis, sarcopenia, mendelian randomization, osteosarcopenia, aging.